Scripture as a Source of Chemnitz’ Christology - Valco, Michal (Communications - Scientific letters of the University of Zilina, 2007)
Martin Chemnitz uses careful exegesis and Biblical scholarship to interpret the relevant texts pertaining to the sacraments in the Scriptures. Though a good systematic theologian, he does not deduce the teaching about the real presence Christ’s body and blood under the elements of the bread and wine in the Lord’s Supper directly from Christology. He uses the Christological teaching only as a necessary metaphysical framework for a thorough interpretation or relevant biblical texts. The sedes doctrinae (the roots and seeds of the doctrine) can be found in the words of institution in the Gospel of Matthew, Mark and Luke. These are the words of Christ himself, which constitute His last will and testament for the church worldwide to follow.